Clinical Strategies Against Early Hematoma Expansion Following Intracerebral Hemorrhage - Tanaka, Kanta; Toyoda, Kazunori (Frontiers in Neuroscience, 2021)
Hematoma volume is the strongest predictor of morbidity and mortality after intracerebral hemorrhage. Protection against early hematoma growth is therefore the mainstay of therapeutic intervention for acute intracerebral hemorrhage, but the current armamentarium is restricted to early blood pressure lowering and emergent reversal for anticoagulant agents. Although intensive lowering of systolic blood pressure to <140 mmHg appears likely to prevent hematoma growth, two recent randomized trials, INTERACT-2 and ATACH-2, demonstrated non-significant trends of reduced hematoma enlargement by intensive blood pressure control, with only a small magnitude of benefit or no benefit for clinical outcomes. While oral anticoagulants can be immediately reversed by prothrombin complex concentrate, or the newly developed idarucizumab for direct thrombin inhibitor or andexanet for factor Xa inhibitors, the situation regarding reversal of antiplatelet agents is not yet quite as advanced. However, considering at most the approximately 10% rate of anticoagulant use among patients with intracerebral hemorrhage, what is most essential for patients with intracerebral hemorrhage in general is early hemostatic therapy. Tranexamic acid may safely reduce hematoma expansion, but its hemostatic effect was insufficient to be translated into improved functional outcomes in the TICH-2 randomized trial with 2325 participants. In this context, recombinant activated factor VII (rFVIIa) is a candidate to be added to the armory against hematoma enlargement. The FAST, a phase 3 trial that compared doses of 80 and 20 g/kg rFVIIa with placebo in 841 patients within 4 hours after the stroke onset, showed a significant reduction in hematoma growth with rFVIIa treatment, but demonstrated no significant difference in the proportion of patients with severe disability or death. However, a post-hoc analysis of the FAST trial suggested a benefit of rFVIIa in a target subgroup of younger patients without extensive bleeding at baseline when treated earlier after stroke onset. The FASTEST trial is now being prepared to determine this potential benefit of rFVIIa, reflecting the pressing need to develop therapeutic strategies against hematoma enlargement, a powerful but modifiable prognostic factor in patients with intracerebral hemorrhage.